Institutional investors and stock market efficiency: The case of the January anomaly - Martin T. Bohl; Katrin Gottschalk; Harald Henke; Rozália Pál (European University Viadrina, The Postgraduate Research Programme: Capital Markets and Finance in the Enlarged Europe, 2006)
In this paper, we investigate the effect of institutional investors on the January stock market anomaly. The Polish and Hungarian pension system reforms and the associated increase in investment activities of pension funds are used as a unique institutional characteristic to provide evidence on the impact of individual versus institutional investors on the January effect. We find robust empirical results that the increase in institutional ownership has reduced the magnitude of an anomalous January effect induced by individual investors' trading behavior.
Keywords: G14; G23; 330; Institutional Traders; Individual Investors; January Effect; Polish and Hungarian Pension Fund Investors